2020
DOI: 10.1007/s10552-020-01301-4
|View full text |Cite
|
Sign up to set email alerts
|

Pesticide use and risk of Hodgkin lymphoma: results from the North American Pooled Project (NAPP)

Abstract: Purpose The purpose of this study was to investigate associations between pesticide exposures and risk of Hodgkin lymphoma (HL) using data from the North American Pooled Project (NAPP). Methods Three population-based studies conducted in Kansas, Nebraska, and six Canadian provinces (HL = 507, Controls = 3886) were pooled to estimate odds ratios and 95% confidence intervals for single (never/ever) and multiple (0, 1, 2-4, ≥ 5) pesticides used, duration (years) and, for select pesticides, frequency (days/year) u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(17 citation statements)
references
References 77 publications
0
17
0
Order By: Relevance
“…Also, recall bias does not appear to be a significant problem in the case-control studies 95 . Furthermore, recall bias cannot be the reason for the elevated NHL risks seen in these studies since no such increases were seen for any of the other cancers studied using the case-control method 4,21,34,35 . Thus, taken together, the epidemiological studies provide ample evidence for a relationship between glyphosate exposure and an increased risk of NHL, and this evidence cannot be simply dismissed due to possible unknown methodological issues or the negative results of questionable cohort studies.…”
Section: Alternative Explanationsmentioning
confidence: 77%
See 2 more Smart Citations
“…Also, recall bias does not appear to be a significant problem in the case-control studies 95 . Furthermore, recall bias cannot be the reason for the elevated NHL risks seen in these studies since no such increases were seen for any of the other cancers studied using the case-control method 4,21,34,35 . Thus, taken together, the epidemiological studies provide ample evidence for a relationship between glyphosate exposure and an increased risk of NHL, and this evidence cannot be simply dismissed due to possible unknown methodological issues or the negative results of questionable cohort studies.…”
Section: Alternative Explanationsmentioning
confidence: 77%
“…These studies have been negative for most of the cancers studied including soft tissue sarcoma, leukemia, multiple myeloma, Hodgkin lymphoma, and cancers of the brain, stomach, esophagus, and prostate. Recent studies of Hodgkin lymphoma and multiple myeloma have also been negative 34,35 . However, most of the studies of NHL have shown an association with glyphosate exposure.…”
Section: Epidemiology In Humansmentioning
confidence: 99%
See 1 more Smart Citation
“…One study reported that, pesticide use was associated with increased risk of developing childhood hematological diseases, including HL and NHL [ 188 ]. Additionally, Latifobic L et al (2020) reported that association between pesticide exposure and HL was higher in subjects less than 40 years [ 189 ]. Interestingly, maternal exposure to insecticides in France (OR 1.6, 1.3-2.1, 95%IC) was related to an increased risk of NHL and HL during childhood [ 190 ].…”
Section: Xenobiotics In Ebv-driven Cancersmentioning
confidence: 99%
“…Over the past century the incidence of non-Hodgkin lymphomas (NHL) has steadily risen, mainly the B-cell lymphomas, as they represent the majority of NHL [1][2][3]. T-cell and NK-cell lymphomas are generally underrepresented due to their low incidence overall.…”
Section: Introductionmentioning
confidence: 99%